Isolation and characterization of gene sequences expressed in cotton fiber - Coutinho, Taciana; Guimarães, Marcelo; Vidal, Marcia (Revista Ciência Agronômica, 2016)
Cotton fiber are tubular cells which develop from the differentiation of ovule epidermis. In addition to being one of the most important natural fiber of the textile group, cotton fiber afford an excellent experimental system for studying the cell wall. The aim of this work was to isolate and characterise the genes expressed in cotton fiber (Gossypium hirsutum L.) to be used in future work in cotton breeding. Fiber of the cotton cultivar CNPA ITA 90 II were used to extract RNA for the subsequent generation of a cDNA library. Seventeen sequences were obtained, of which 14 were already described in the NCBI database (National Centre for Biotechnology Information), such as those encoding the lipid transfer proteins (LTPs) and arabinogalactans (AGP). However, other cDNAs such as the B05 clone, which displays homology with the glycosyltransferases, have still not been described for this crop. Nevertheless, results showed that several clones obtained in this study are associated with cell wall proteins, wall-modifying enzymes and lipid transfer proteins directly involved in fiber development.